Time Portals, Love Machines, Land Oracles: Hybrid Geography and the Situated Digital. (2nd January 2020) - Waterman, Tim
Abstract: London‐based digital art collective Furtherfield creates events and space that encourage cultural flowering through the celebration of difference and otherness. Executive director Tim Waterman, a senior lecturer in landscape history and theory at the Bartlett School of Architecture, University College London, takes us on a journey, starting with the organisation's inception, then projecting us into the future with an outline of its projects for the next few years.